Raman spectroscopy in the characterization of autochthonous sweet cherry (Prunus avium L.) cultivars from the Balkan region - Volić Mina M.; Obradović Nataša S.; Milivojević Ana D.; Milošević Nebojša T.; Pećinar Ilinka M. (Journal of Agricultural Sciences (Belgrade))
The quality assessment and evaluation of fruits and vegetables are crucial in their postprocessing, shelf life, and price. Most of the techniques applied to evaluate fruit and vegetable quality are invasive. However, there is a growing interest in non-invasive techniques for assessing fruit quality, which are gaining traction due to their application and operation mechanism. The present study demonstrates, for the first time, the applicability of the Raman spectroscopy for spectral signature assessment of sweet cherry (Prunus avium L.) cultivars ('Đuti', 'Canetova', 'Ohridska crna', and 'Dolga Šiška'). Combined with principal component analysis (PCA), Raman spectroscopy was used in assessing nutritionally similar samples, such as the studied sweet cherry cultivars. Sugars (glucose, sucrose, and fructose), anthocyanins, phenolic acids, and flavonoids, quantified by comparison to reference standards using high-performance liquid chromatography, exhibited Raman bands (at 337, 399, 455, 538, 617, 1327, and 1600 cm-1 , respectively) of varying intensities, indicating differences among cultivars. Compared to the other cultivars, the 'Ohridska crna' cultivar had the highest nutritional and health-promoting compounds. A correlation was found between the Raman bands and the sugar and phenolic content obtained by chemical analysis. The results indicate the applicability of chemometric modeling associated with Raman spectroscopy for rapid sweet cherry authentication.